Pengolahan Data Arsip Putusan Hukum di Kantor Pengadilan Tinggi Padang Menggunakan Microsoft Access - Safitri, Putri Novia; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of writing this paper is to describe how the verdict can archive data processing using Microsoft Access program at the Office of the High Court of Padang. The method used in this paper is the observation and direct participation by collecting data from the original source. Treatment process begins with the entry of data into the Microsoft Access table, design table with Form Design medesign thus become more attractive appearance and create Query. Query was created as a tool to search the data, because queries can answer questions on the data in question. Making Query in Microsoft Access only put one formula on Parameter Query and Query straight to work. Working with Query makes the search easy and fast. Keywords: data; records; law; Microsoft Access; query. Â